Spasm : a novel [compact disc, unabridged] - Cook, Robin, 1940- (Jack Stapleton & Laurie Montgomery, 2025)
When an old med-school classmate asks for help explaining an odd death in upstate New York, Jack Stapleton and Laurie Montgomery see a mystery and vacation in one. But when the body vanishes pre-autopsy, the stakes increase.